Opuntia ficus-indica (L.) Mill. and Annona cherimola Mill. by-products: a potential to be exploited - Pereira, P. (2019)
Introduction: Fruits have become increasingly important in human nutrition because of their nutrient and bioactive composition, as well as potential beneficial health effects. Opuntia ficus-indica (L.) Mill. and Annona cherimola Mill. are commonly known as prickly pear and cherimoya, respectively. These exotic fruits are highly appreciated due to their attractive sensorial properties (1). However, considerable quantities of by-products from the production of these fruits are discarded, and these can be a valuable source of bioactive compounds. Therefore, this study aims to perform a comparison between the antioxidant activity, total phenolics, total flavonoids and vitamin C contents of the peels of prickly pear and cherimoya, in order to evaluate their potential to obtain added value natural extracts. Materials and Methods: Samples of cherimoya were supplied by a company located in Madeira Island (Portugal) and samples of prickly pear were obtained at Herdade de Peliteiros (Silveiras, Montemor-o-Novo, Évora, Portugal). Then, samples were manually divided between edible portion (pulp) and non-edible portion (peel). Peels of the selected fruits were analysed concerning: (i) antioxidant activity by radical 2,2-diphenyl-1-picrylhidrazyl (DPPH•) scavenging activity method; (ii) total phenolics determined by Folin-Ciocalteu assay and expressed as mg of gallic acid equivalents (GAE)/g of sample; and (iii) total flavonoids, expressed as mg of epicatechin equivalents (ECE) per g of sample, through the interpolation of the calibration curve of epicatechin (2). Total vitamin C content was determined by high performance liquid chromatography coupled to diode array detection. All analyses were performed in triplicate (1). Results: EC50 is the concentration of the sample that decreases the initial DPPH• absorbance by 50%. Therefore, the highest antioxidant activity was observed for the peel of cherimoya (EC50, 0.18 ± 0.0 mg/mL). With respect to total phenolics, the obtained values were 0.195 ± 0.01 and 49.1 ± 1.0 mg of GAE/g of sample, for cherimoya and prickly pear peels, respectively. Also, prickly pear peel showed the highest total flavonoids content (3.01 ± 0.14 mg ECE/g) and total vitamin C content (132.4 ± 0.61 mg/100 g of sample). Discussion and Conclusions: These results highlight the antioxidant properties of these by-products and support their employment as added value natural extracts in cosmetic, pharmaceutical and food processing industries. Furthermore, this work will contribute to maintain the biodiversity and to promote the sustainable development and exploitation of these exotic fruits.